2017
DOI: 10.1021/acs.chemrestox.6b00336
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approach to Structural Alerts: Furans, Phenols, Nitroaromatics, and Thiophenes

Abstract: Structural alerts are commonly used in drug discovery to identify molecules likely to form reactive metabolites and thereby become toxic. Unfortunately, as useful as structural alerts are, they do not effectively model if, when, and why metabolism renders safe molecules toxic. Toxicity due to a specific structural alert is highly conditional, depending on the metabolism of the alert, the reactivity of its metabolites, dosage, and competing detoxification pathways. A systems approach, which explicitly models th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 110 publications
1
52
1
Order By: Relevance
“…2016), involving the physicochemical and reactivity properties of the chemicals [read-across and quantitative structure–activity relationships (QSARs)]. Both are important for the interactions with specific biological targets and pathways, and therefore allow the prediction of toxic effects (Dang et al. 2017; Zang et al.…”
Section: Discussionmentioning
confidence: 99%
“…2016), involving the physicochemical and reactivity properties of the chemicals [read-across and quantitative structure–activity relationships (QSARs)]. Both are important for the interactions with specific biological targets and pathways, and therefore allow the prediction of toxic effects (Dang et al. 2017; Zang et al.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Likewise, alert structures are commonly used to identify liabilities in molecule structure, 1517 and we previously demonstrated that metabolism models can improve the specificity of alerts. 18 The hope is that modeling of metabolism and reactivity will improve substantially on purely statistical approaches to understanding toxicity, as are commonly relied upon within industry and regulatory agencies. 19 Metabolism modeling with machine learning does not produce detailed enzyme mechanics, but they do provide finer grain information that is currently used, and for this reason are a significant step forward.…”
Section: Introductionmentioning
confidence: 99%
“…2 ; Table 1 ; Supplementary Table 1 ). However, it is also reported that the occurrence of the drug-induced toxicities depends on many factors such as dosage, metabolites reactivity, structural alert metabolism, competition for detoxification pathways, and individual differences between patients [ 3 , 22 24 ]. The results of the analyses have also shown that the majority of the drugs (72%) were potentially reactive, unstable or toxic, and 70% of them were also potentially toxic at normal treatment concentrations, based on their doses or LD-50 values evaluation (Supplementary Table 1 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that structural alerts do not predict metabolism and toxicity adequately. Therefore, some medicines may be designated as safe or unsafe when actually it is not true [ 3 , 22 ]. The drug-induced toxicities caused by structural alerts and reactive metabolites may be caused by either covalent interactions or noncovalent interactions with cellular macromolecules such as DNA, proteins and lipids [ 27 ], but in many cases their exact mechanism is not known [ 3 , 22 ].…”
Section: Discussionmentioning
confidence: 99%